Legislative bargaining with costly communication - Merkel, Anna; Vanberg, Christoph (Public choice, 2020)
We investigate the effects of voting rules on delay in a multilateral bargaining experiment with costly communication. Our design is based on a variant of the Baron-Ferejohn framework. Communication takes place after a proposer is selected and before a proposal is made. In contrast to prior experiments, communication is directly associated with costs in our setup. Specifically, every second of communication increases the probability that the game is terminated before a proposal can be made. In case of ‘breakdown’, each player receives an exogenously fixed disagreement value. Those values sum up to less than the amount of the available surplus, implying that delay owing to communication is costly. We vary the decision rule (majority versus unanimity) as well as the distribution of disagreement values (symmetric or asymmetric). We find that unanimity rule leads to longer communication delays and more frequent breakdowns in asymmetric, but not in symmetric situations.